EXAMINING THE ANOMALY OF AN IMPERFORATED HYMEN IN A HOLSTEIN FRIESIAN HEIFER: A SCARCE AND INTRICATE CASE - Sharma, Roberts; Singh, Kumar (International Journal of Allied Sciences (IJAS), 2022)
An atypical and intricate case came to light when a 20-month-old Holstein Friesian heifer presented with an obstruction in its genital tract during an artificial insemination procedure carried out by a field veterinarian. The animal displayed a regular oestrous cycle without any signs of cervico-vaginal discharge during oestrus, which added to the complexity of the case. A per vaginal examination exposed a thick muscular band located in front of the external urethral orifice, which was subsequently diagnosed as an imperforated hymen. To address this seldom-seen hymenal defect, a trocar was employed to create a perforation, followed by dilation through digital pressure. In this 300-word abstract, the various facets of this extraordinary case are thoroughly examined, shedding light on the diagnostic and treatment methods used to manage such an infrequent condition in a Holstein Friesian heifer.